Administration of Human Recombinant Activated Protein C Is Not Associated with Pancreatic Parenchymal Haemorrhage in L-Arginine-Induced Experimental Acute Pancreatitis - Jamdar, Saurabh; Babu, Benoy I; Nirmalan, Mahesh; Jeziorska, Maria; McMahon, Raymond F T; Siriwardena, Ajith K (JOP. Journal of the Pancreas, 2013)
Context Microvascular thrombosis is a critical event in severe acute pancreatitis. Human recombinant activated protein C (Xigris®, Eli Lilly, Indianapolis, IN, USA) modulates the interplay between pro-inflammatory and pro-coagulant pathways and maintains microvascular patency. However, the anticoagulant properties of Xigris® may precipitate bleeding from the inflamed pancreas. Objective This study tests the hypothesis that Xigris® can ameliorate experimental acute pancreatitis without causing pancreatic haemorrhage. Methods Sprague Dawley rats were allocated as follows: Group 1: control (n=7); Group 2: acute pancreatitis (n=6); Group 3: administration of Xigris® 500 µg/kg body weight before induction of acute pancreatitis (n=6); and Group 4: Administration of Xigris® 500 µg/kg body weight 30 minutes after induction of acute pancreatitis (n=6). Acute pancreatitis was induced by intraperitoneal administration of L-arginine 300 mg/100 g body weight. Animals were sacrificed at 48 hours and biochemical, haematological, and histological markers of pancreatic haemorrhage and inflammation assessed. Results Median lipase in animals with acute pancreatitis was 10 U/mL (range: 7-16 U/mL) compared to 5.5 (range: 3-8 U/mL) in controls (P=0.028). Lipase was also elevated in animals given Xigris® both before (12 U/mL, range: 8-22 U/mL; P=0.031 vs. control group) and after (46 U/mL, range: 9-71 U/mL; P=0.015 vs. control group) induction of acute pancreatitis). Haemoglobin levels were similar among all groups (P=0.323). There was no histological evidence of pancreatic haemorrhage in animals treated with Xigris®. Pre-treatment with Xigris® was associated with a significant reduction in pancreatic injury. This effect was absent when Xigris® was administered after induction of acute pancreatitis. Conclusion Xigris® did not lead to pancreatic haemorrhage in experimental acute pancreatitis. Administration of Xigris® prior to induction of acute pancreatitis was associated with amelioration of injury. This effect was not seen with administration of Xigris® after induction of acute pancreatitis. Image: Composite pancreatic histological injury score.